Students' Perceptions of English Language Learning Game-Based: A Case Study of Google Quizzes - Annasthasya Yudha Putri; Wawan Setyawan; Anggga Prasongko (LP. Ma'arif Janggan Magetan, 2024)
In today's digital age, English language learning is growing, with various methods and approaches used to improve teaching effectiveness. One method that is gaining popularity is game-based learning, which utilizes game elements to create a more engaging and interactive learning atmosphere. Therefore, The purpose of the problem formulation regarding the experience of using Google Quizizz in English language learning is to explore its impact on grade 6 students' comprehension of the material, motivation, and enthusiasm for learning. It is important to understand students' perceptions of this technology-based learning method. Google Quizizz is implemented as an interactive learning tool where teachers create quizzes according to teaching materials. Students take the quiz in a competitive and fun atmosphere, stimulating their spirit to try better. After the quiz, the teacher analyzes the results to provide feedback and to see areas of understanding that need improvement. Student responses to using Google Quizizz are generally positive; many feel more motivated to learn English. The game element in the quiz makes the learning experience more interesting and less boring. In this way, students actively participate in the learning process, creating a dynamic classroom atmosphere. Overall, the implementation of Google Quizizz positively impacted students' motivation and passion for learning. With good preparation and implementation, this application can be an effective tool for educators to create an interactive learning environment. This research is expected to provide recommendations for educators to continue integrating technology in education to improve the quality of learning in Indonesia. One widely used platform in this context is Google Quizizz, which allows teachers to create interactive quizzes that students can access online. This study used a descriptive qualitative approach with 29 students as participants. The instruments used were observation, interview, and literature study. The results showed that using Google Quizizz game-based learning can increase learning motivation and understanding of English materials.